Indonesian local fetal-weight standard: a better predictive ability for low Apgar score of SGA neonates (Faculty of Medicine Universitas Indonesia, 2016)
Background: Accurate assessment of fetal growth is one of crucial components of antenatal care. A generic reference for fetal-weight and birthweight percentiles that can be easily adapted to local populations have been developed by Mikolajczyk and colleagues. This study aimed to validate our own local percentile standard by evaluating the odds ratio (OR) of low 1st and 5th minute Apgar score for small-for-gestational age (SGA) versus those not SGA. Methods: We used the generic reference tools for fetal-weight and birthweight percentiles developed by Mikolajczyk and colleagues to create our own local standard and then defined the SGA neonates. For validation, we used the database of singleton live deliveries (2,139 birth) during January 1st to December 31st 2013 in Cipto Mangunkusumo Hospital, Jakarta, Indonesia. We compared our reference with that of Hadlock and colleagues. For every reference, the OR of Apgar score <7 at 1st and 5th minutes for infants who were SGA versus those not estimated with bivariate and multivariate analyses. Results: SGA found in 35% (748/2,139) and 13% (278/2,139) of neonates using the definition derived from Indonesian standard and Hadlock's. OR of Apgar score <7 at 1st and 5th minutes were 3.45 (95% CI=2.56–4.65) and 3.05 (95% CI=1.92–4.83) for the Indonesian local fetal-weight standard compared with respectively 2.14 (95% CI=1.65–2.76) and 1.83 (95% CI=1.21–2.77) for Hadlock and collegues' reference. Conclusion: Indonesian local fetal-weight standard has a better ability to predict low 1st and 5th minutes Apgar scores of SGA neonates than has the Hadlock and collegues' reference.